Teori Humanistik dan Implikasinya dalam Pembelajaran Pendidikan Agama Islam - Haryati, Mita; Rahmania, Elvina; Lorens, Xena; Harto, Kasinyo; Pratama, Irja Putra (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
This research aims to analyze the implementation of humanistic theory and its impact on cognitive, emotional, and spiritual aspects. Students feel happy and enthusiastic, take the initiative in learning, experience changes in mindset, behavior, and attitude of their own accord without pressure or coercion, and are helped to develop their potential to the fullest. The teacher acts as a facilitator who supports students in a meaningful learning process. The humanistic theory positions students as unique, active, and valuable individuals in the learning process. This research uses a qualitative library research method with a descriptive-analytical approach by collecting sources from various relevant books and articles. In Indonesia, learning objectives are determined by teachers based on established educational standards. For the methods and media to be used, they can be agreed upon by the teacher and the students. This approach also emphasizes the importance of creating an inclusive and empathetic learning environment, where students feel valued and accepted, and encourages them to internalize Islamic values in their daily lives. The results of this study indicate that the implementation of humanistic theory can enhance students' intrinsic motivation, deepen their understanding of Islamic teachings, and encourage them to apply these values in social and spiritual interactions.